A profile of the sewers of a selected small scale and medium scale garment factory - Sandoval, Marisol Sarmenta
This paper aims to establish a profile of the sewers of a selected small scale and medium scale garment factory. The profile includes the individual difference factors, situational variables, and job satisfaction. A guide questionnaire translated into Filipino / Tagalog, was utilized during the interview. The study indicated that the manpower characteristics are: socio-demographically garment factory sewers belong to 20-28 age bracket and female. Civil status varies deeply on company policy, for a company with stay-in policy the sewers are single, however, a non-stay-in sewer is most likely to be married. Almost all are Roman Catholics and had finished high school. Under place of birth, Nueva Ecija stands out in the medium scale factory. However, the small scale garment factory wherein five samples were accounted for had 4 places of birth thus it was difficult to come up with a general conclusion. Residence for the first fifteen years of their life is dominantly same as the place of birth. For single sewers, their income are considered merely as added family income. On the other hand, married sewers definitely have their children as dependents. Twelve out of twenty-five have been staying in Metro Manila between 1-5 years. Most have no vocational training related to sewing as well as working experience as a sewer prior to the company currently working with, however, the small scale garment factory sewers already had prior working experience as a sewer. No. 1 motivators are the company's reputation, importance given by the management to the sewers, and the sewers drive to succeed. Benefits and management style are not motivators for the workers most especially for the medium scale factory sewers. The number one aspiration is a happy family and the last on rank are to gain importance in the society and to have successful children for medium scale garment factory sewers. Moreover, a small scale garment factory sewers consider economic security and having one's own business as the highest aspirations in life. The sewers are educationally, physically, mentally and skillfully suitable for their type of work. P1,000 is the lowest average wage and P4,000 is the highest average monthly wage. Majority receives P2,500 per month. Manner of payment is basically piece rate. Payment interval depends on company policy, even fifteen days for the medium scale factory and weekly for the small scale sewers have an average no. of more or less 5 years in the company. Four out of five respondents in the small scale factory are very new to the company. A lot of sewers are satisfied with the opportunity to have a better life in terms of having one's one business, a wage increase, and promotion; physical working environment; the company they are currently working with; and last but not the least, their being a sewer.